EXPERIENCES OF SECONDARY TRAUMA AMONGST SPOUSES OF EMERGENCY SERVICE PERSONNEL - Wheater, Kerry; Erasmus, Charlene (Social Work/Maatskaplike Werk, 2017)
<span style="color: black; font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">This article explored the <span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">secondary trauma<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> experiences of the spouses of medical emergency service personnel (ESP)<span style="color: black; font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">. <span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Eight spouses of ESP were interviewed and this produced five themes. S<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">ome of the EMS personnel bring their caring and supportive nature into the relationship and use the insight learnt in their role to benefit the relationship<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">. <span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Negative impacts of emergency work on relationships were increased arguments, decreased quality time, distancing from spouses, communication breakdown and fewer social activities. <span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Secondary trauma is characterised by fears about safety of their spouse, behaviour changes from living with their spouses’ emotional reactivity, and social withdrawal from family members.